Zooarchaeological and Stable Isotopic Assessments on Pinniped-Human Relations in the Beagle Channel (Tierra del Fuego, Southern South America) - Zangrando, Atilio Francisco Javier (2013)
Recent zooarchaeological investigations in the Beagle Channel region have shown long-term variations characterised by a high inter-taxonomic dominance of pinnipeds during the first moments of the archaeological sequence (ca 6400 bp) at the Túnel Locality and a decrease in the relative importance of this resource and a diversification of subsistence in that place since 5500 bp. Two possible explanations for these variations are evaluated: (i) variations in foraging habits of pinnipeds that would lead to changes in the degree of predictability or access to the resource and (ii) a reduction in resource availability because of increased human predation pressure. To analyse these arguments, this paper presents and discusses the results of an analysis of stable isotopes (δ13C and δ15N) from collagen samples of South American fur seals (Arctocephalus australis) and representations of age and size of pinnipeds in the archaeological record of Túnel. Stable isotope analyses suggest that there were variations in the foraging behaviour of southern fur seals at the same time that zooarchaeological analyses record decreases of the ages and sizes of the hunted prey. On the basis of these results, an increase of hunter-gatherer predation pressure on pinnipeds to the Middle-Late Holocene in southern South America is suggested.